Epidemiology of diabetes mellitus in South America: The experience of Colombia (2016)
According to the International Diabetes Federation, 8.3% of the world population suffers from diabetes mellitus, and it is expected that the number of individuals with the disease will increase to over 592 million. In South and Central America, it is estimated that the increase in the number of cases diagnosed in the period from 2013 to 2035 will be 59.8% (from 24 to 38.5 millions). According to the World Health Organisation, the prevalence of fasting hyperglycaemia in the region of the Americas in 2014 was 9.3% in men and 8.1% in women. The countries with the highest prevalence of diabetes mellitus in adults ≥ 18 years were: Guyana, Surinam, Chile, and Argentina. In Colombia, the prevalence of type 2 diabetes mellitus is variable, depending on the population range assessed and the diagnostic criteria used. © 2016 Sociedad Española de Arteriosclerosis